CMOS Image Sensor Based Physical Unclonable Function for Coherent Sensor-Level Authentication - Cao, Yuan (2016)
In the applications of biometric authentication and video surveillance, the image sensor is expected to provide certain degree of trust and resiliency. This paper presents a new low-cost CMOS image sensor based physical unclonable function (PUF) targeting a variety of security, privacy and trusted protocols that involves image sensor as a trusted entity. The proposed PUF exploits the intrinsic imperfection during the image sensor manufacturing process to generate unique and reliable digital signatures. The proposed differential readout stabilizes the response bits extracted from the random fixed pattern noises of selected pixel pairs determined by the applied challenge against supply voltage and temperature variations. The threshold of difference can be tightened to winnow out more unstable response bits from the challenge-response space offered by modern image sensors to enhance the reliability under harsher operating conditions and loosened to improve its resiliency against masquerade attacks in routine operating environment. The proposed design can be classified as a weak PUF which is resilient to modeling attacks, with direct access to its challenge-response pair restricted by the linear feedback shift register. Our experiments on the reset voltages extracted from a 64 × 64 image sensor fabricated in 180 nm 3.3 V CMOS technology demonstrated that robust and reliable challenge-response pairs can be generated with a uniqueness of 49.37% and a reliability of 99.80% under temperature variations of 15∼ 115°C and supply voltage variations of 3∼ 3.6V